Effect of Enzyme Supplementation of Palm Kernel Meal and Brewer`s Dried Grain on the Performance of Broilers - Iyayi, Eustace A.; Davies, Bina I. (International Journal of Poultry Science, 2005)
Seventy-two male broiler chickens were randomly distributed into groups of 6 totaling 12 groups. Three diets (Diet 1-Basal, maize-based with no enzyme; Diet 2-BDG + Enzyme-based and Diet 3-PKM + Enzyme-based) were formulated and randomly offered to any 4 of the groups. The aim was to compare the performance of the birds on the enzyme supplemented high fibre diets with those on the maize-based diet with no enzyme supplementation. Weight gain and feed intake were significantly (p